2008
DOI: 10.1016/j.febslet.2008.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock protein Hsp27 protects myosin S1 from heat‐induced aggregation, but not from thermal denaturation and ATPase inactivation

Abstract: We applied different methods, such as turbidity measurements, dynamic light scattering, differential scanning calorimetry and co-sedimentation assay, to analyze the interaction of small heat shock protein Hsp27 with isolated myosin head (myosin subfragment 1, S1) under heat-stress conditions. Upon heating at 43°C, Hsp27 effectively suppresses S1 aggregation, and this effect is enhanced by mutations mimicking Hsp27 phosphorylation. However, Hsp27 was unable to prevent thermal unfolding of myosin heads and to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Thus, posttranslational modifications of the N-terminal domain can significantly affect the quaternary structure of the small heat shock proteins. Phosphorylation affects the chaperone-like activity of Hsp27 and its orthologs, however the amplitude and the sign of this effect seem to depend on experimental conditions and on the nature of model target proteins used in experiment [77,85,86,88,89].…”
Section: N-terminal Domain Of Small Heat Shock Proteinsmentioning
confidence: 94%
“…Thus, posttranslational modifications of the N-terminal domain can significantly affect the quaternary structure of the small heat shock proteins. Phosphorylation affects the chaperone-like activity of Hsp27 and its orthologs, however the amplitude and the sign of this effect seem to depend on experimental conditions and on the nature of model target proteins used in experiment [77,85,86,88,89].…”
Section: N-terminal Domain Of Small Heat Shock Proteinsmentioning
confidence: 94%
“…Some in vitro studies concluded that the unphosphorylated oligomeric Hsp27 (or the murine isoform Hsp25) protects proteins against aggregation better than does the phosphorylation mimic (13,19,27), whereas others found no difference (16,28,29), and still other studies found that the mimic protects better than does the unphosphorylated wild type (27,30,31). In-cell studies found that phosphorylation of Hsp27 was essential for thermo-protection of actin filaments (32), and the Hsp27 phosphorylation mimic decreased inclusion body formation better than did unphosphorylated Hsp27 (33).…”
mentioning
confidence: 99%
“…In this respect, Hsp22 is quite different from all other mammalian sHsp studied by DSC, e.g. Hsp27 and α-crystallin, which demonstrated cooperative thermal transitions at~70°C for Hsp27 [25,33,34] and at 60°C for α-crystallin [35,36]. This indicates that Hsp22, in contrast with Hsp27 and α-crystallin, lacks rigid tertiary structure.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, Hsp27-3D that unfolds at temperature higher than 70°C [25,33,34] is the most effective, whereas the wild type Hsp22 and especially its K141E mutant undergoing thermal unfolding at about 58 and 51°C are less effective in retarding F-actin aggregation that starts at about 55°C (Fig. 6).…”
Section: Effect Of Hsp22 and Its K141e Mutant On Heat-induced Aggregamentioning
confidence: 94%